High and low credit risk in SME portfolios: Evidence from regulatory risk grade dissemination - Jan Nokkala (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2022)
Purpose: SME sector credit risk has received attention in research from several dimensions of the financial system. SME sector's funding is mainly supplied by financial institutions and SME sector is both diversified and large sector in both well developed and less developed economies. Specific research on assessing SME as Financial Institution's (FI's) individual counterparties and SMEs as portfolios have developed from a theoretical and empirical perspective. To supplement current research on the area, we approach SME risk from perspective of FIs own risk assessments and compare it to how SME risk rating and measurement compares to other counterparties. Design/methodology/approach: We use published risk rating data from large financial institutions in Europe including globally operating FIs and compare shares of credits in different risk grades and overall portfolio risks within an institution's own risk classification system and risk measurement system. The data consists of 89 comparable portfolios with over 25 million credits. Findings: Our results show that comparison to households and large corporates originates from higher default rate estimates for SME, which shows as smaller share of credits in the investment grade. SME risk is further raised as even within speculative grades SME's receives higher default estimates in comparison to households and large corporates. An equally notable finding is that the other relevant parameter for risk calculation, loss given default (LGD), does not differ between SME's and other counterparties. A part of SME credits is found to be in a low-risk regime in portfolio credit risk estimation. Research limitations/implications: Coverage and detail of data restricts to a specified geographical coverage and aggregated data on SME-companies is not as exact as unit level data. The data represents mostly European institutions as it is collected from institutions which have a head quarter in Europe and are applying Basel regulation in a single rule book environment for banking regulation. In a global scope there may be differences between jurisdictions or between geographical areas. Data published by institutions is an aggregated data on a rating grade level a and not on a unit level data that institutions have for their exact calculations. Comparison methods for SME sector are selected accordingly so that methods apply to class level instead of unit level data. Originality/value: Higher capital requirements for SME's may restrict the price and availability of finance. According to our results there can be separated a low-risk SME finance without higher capital requirements compared to peers. Results may also be used to support counterparty level default risk model results showing higher risk for SME's which can be seen in smaller shares of investment grade credits and in a higher default rate for speculative grade credits.
Keywords: G11; G18; E51; 330; Credit risk; SME finance; Banking regulation; Risk models; Ratings